Education In the COVID 19 Pandemic at The University: Chances And Dangers - Marek Walancik (Communications of International Proceedings, 2022)
The biggest challenge for institutions involved in the process of educating schools and universities in the first phase of the pandemic was to launch remote classes on a very large scale, and in the lockdown period - completely in a very short time. In the presented text, on the basis of research, I present how WSB University in Poland organized the educational process during the pandemic. What was the level of acceptance of the adopted (implemented) legal, organizational, didactic and other solutions enabling the implementation of the University's tasks in the time of the Sars-Cov-2 pandemic? What benefits and threats have been noticed by the teaching staff due to the remote teaching model adopted at the university in the time of the COVID 19 pandemic? What solutions implemented in the pandemic at the University would be left after the COVID 19 pandemic?
Keywords: education; COVID 19 pandemic; distance learning; threats; benefits